Glycine increases fat‐free mass in malnourished haemodialysis patients: a randomized double‐blind crossover trial. Issue 6 (14th September 2021) - Genton, Laurence; Teta, Daniel; Pruijm, Menno; Stoermann, Catherine; Marangon, Nicola; Mareschal, Julie; Bassi, Isabelle; Wurzner‐Ghajarzadeh, Arelene; Lazarevic, Vladimir; Cynober, Luc; Cani, Patrice D.; Herrmann, François R.; et al.
Abstract: Background: Protein energy wasting is associated with negative outcome in patients under chronic haemodialysis (HD). Branched‐chain amino acids (BCAAs) may increase the muscle mass. This post hoc analysis of a controlled double‐blind randomized crossover study assessed the impact of BCAAs on nutritional status, physical function, and quality of life. Methods: We included 36 chronic HD patient features of protein energy wasting as plasma albumin <38 g/L, and dietary intakes <30 kcal/kg/day and <1 g protein/kg/day. Patients received either oral BCAA (2 × 7 g/day) or glycine (2 × 7 g/day) for 4 months (Period 1), followed by a washout period of 1 month, and then received the opposite supplement (Period 2). The outcomes were lean body mass measured by dual‐energy X‐ray absorptiometry, fat‐free mass index measured by bioelectrical impedance, resting energy expenditure, dietary intake and appetite rating, physical activity and function, quality of life, and blood parameters. Analyses were performed by multiple mixed linear regressions including type of supplementation, months, period, sex, and age as fixed effects and subjects as random intercepts. Results: Twenty‐seven patients (61.2 ± 13.7 years, 41% women) were compliant to the supplementations (consumption >80% of packs) and completed the study. BCAA did not affect lean body mass index and body weight, but significantly decreased fat‐free mass index, as compared with glycine (coeff −0.27, 95% confidence interval −0.43 to −0.10, P = 0.002, respectively). BCAA and glycine intake had no effect on the other clinical parameters, blood chemistry tests, or plasma amino acids. Conclusions: Branched‐chain amino acid did not improve lean body mass as compared with glycine. Unexpectedly, glycine improved fat‐free mass index in HD patients, as compared with BCAA. Whether long‐term supplementation with glycine improves the clinical outcome remains to be demonstrated.